REPRESENTASI KESANTUNAN TINDAK TUTUR BERBAHASA INDONESIA DALAM PEMBELAJARAN DI KELAS (KAJIAN ETNOGRAFI KOMUNIKASI) - -, Syahrul R. (Diksi, 2008)
This article is about a research study conducted to describe and clarifypoliteness in speech acts using Indonesian in the talk done during a lesson in theclassroom at SMA PMT Hamka, a senior high school in Padang Pariaman,Sumatra Barat, focusing on representations of (1) the forms of politeness in thespeech acts, (2) the functions of politeness in the speech acts, and (3) the strategiesof using politeness in the speech acts. It was a case study with communicationethnography and pragmatics as its starting points. The data consisted of two types:data from utterances and data from field notes. The two types of data, compiled bymeans of recordings, observations, and interviews, were analyzed with aninteractive model of analysis.The research findings are as follows. First, in the context ofrepresentations of the forms of speech-act politeness, it is found that (a) suchrepresentations using Indonesian use the declarative, interrogative, and imperativemodes, (b) the use of the declarative mode represents command, request, advice,and praise, (c) the use of the interrogative mode represents requesting, asking forwhat students have promised, clarifying whether students have understood, andgiving a warning, (d) the use of the imperative mode represents invitation to dosomething, request, and command, (e) a softening of the illocution power is foundin utterances using the declarative and interrogative modes so that the utterancesare felt to be polite, (f) utterances using the interrogative mode, however, tends tohave a strengthening effect on the illocution power so that the utterances are feltless polite. Second, in the context of representations of the functions of speech-actpoliteness, it is found that (a) the functions of politeness in directive acts consist ofrequesting, permitting, advising, commanding, and forbidding functions and (b)the functions of politeness in expressive acts consist of praising and thankingfunctions. Third, in the context of representations of the strategies of speech-actpoliteness, it is found that (a) utterances can be direct, realized in completeimperative form and imperative form with incomplete phrase and (b) utterancescan be indirect by (1) being with expressions of politeness used in a positive way,(2) being with expressions of politeness used in a negative way, and (3) beingunclear.Keywords: politeness, speech act, directive, expressive, classroom instruction120